Standardized Approach to Life History Data Collection in Poeciliid Fishes - Erik S. Johnson (Ecology and Evolution)
ABSTRACT Livebearing fishes in the family Poeciliidae have been essential to testing life history theory. These species are remarkable because males internally inseminate females, and females give birth to free‐swimming young, making these fishes amenable to investigating the evolution of a variety of life history traits, including the timing and nature of maternal reproductive investment, timing of maturity, strategies for maternal provisioning of embryos, and several other classic life history traits. However, researchers vary in the methods that they use to measure these traits, making it difficult to compare findings across studies. Here, I present a standardized approach to studying life history traits in livebearing fishes. I describe methods for preserving samples in the field, for collecting data on a standard set of life history traits, and for processing data in ways that will allow comparisons among studies. I highlight different options in preservation techniques and in data collection that are dependent on the specific questions being addressed. Finally, I argue for a standard approach moving forward to make it possible to complete large‐scale comparative studies to reveal how life history traits have evolved in this important model system.